The effect of service quality on saving decisions with Islamic branding as a moderating variable - Suprapto, Fitria Magdalena (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
As the largest Muslim country in the world, Indonesia is a potential producer market. To maintain and increase consumer confidence in a product is the quality of service. One of the strategies used by business actors, including banks, is implementing an Islamic branding strategy, namely using an Islamic identity in marketing their products. This study examines the effect of service quality on saving decisions with Islamic branding as a moderating variable. This type of quantitative research uses a sample of 94 respondents. The data were collected using a cross-sectional questionnaire distributed. While, statistical testing of research data uses PLS-based Structural Equation Modeling. The study’s results support the first hypothesis that the service quality variable significantly affects saving decisions. While the second hypothesis is that Islamic branding variables moderate the relationship between service quality and saving decisions. The results of this study can assist business actors in improving service quality.